Formation in married life: A comparative study in the Diocese of Changzhi - Li, Yan Peng; Tan, Carmen M.; Cordova, Romelle S. (Technium Social Sciences Journal, 2025)
This study, "Formation in Married Life: A Comparative Study in the Diocese of Changzhi," discuss the effects of pre-marriage and post-marriage programs of changzhi diocese on married couples. The study aims to compare the marriage life of couples who joined the programs and those who did not. The paper is based on Catholic teachings, especially from Pope John Paul II’s "Familiaris Consortio," Pope Francis’s "Amoris Laetitia," and the Vatican’s "Catechumenal Pathways for Married Life." These teachings stress the importance of spiritual preparation and support before and after marriage. They aim to make marriages stronger and families more peaceful. The study used stories from interviews with six couples. Three couples joined the programs, and three did not. The study shows big differences in how they understand marriage, communicate, and solve problems. Couples who joined the programs communicate better, have a deeper spiritual bond, and solve conflicts more easily. This helps create a more peaceful and stable marriage. The study concludes that marriage programs improve marriage quality and gives ideas to help the diocese make these programs better.